2020
DOI: 10.7554/elife.62554
|View full text |Cite
|
Sign up to set email alerts
|

Variation of connectivity across exemplar sensory and associative thalamocortical loops in the mouse

Abstract: The thalamus engages in sensation, action, and cognition, but the structure underlying these functions is poorly understood. Thalamic innervation of associative cortex targets several interneuron types, modulating dynamics and influencing plasticity. Is this structure-function relationship distinct from that of sensory thalamocortical systems? Here, we systematically compared function and structure across a sensory and an associative thalamocortical loop in the mouse. Enhancing excitability of mediodorsal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 110 publications
3
30
0
Order By: Relevance
“…Interestingly, in humans other brain disorderscharacterized by strong deficits in cognition -have been often associated with altered PFC excitation including spindles density and changes in the structure and/or activity of the medial thalamus (19,(94)(95)(96). These investigations are further supported by the high density of medial thalamic projections to frontal cortical regions, while other thalamic nuclei preferentially regulate activity of more parietal cortices (18,22,25,26,61,97). Here, we found a negative correlation between frontal spindles density and working memory performance that highlight the circuit specificity of our Opto-STROKE model and further supports the notion that these two phenomena might be functionally related and dependent on IL-PFC projections integrity (Figure 5M).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, in humans other brain disorderscharacterized by strong deficits in cognition -have been often associated with altered PFC excitation including spindles density and changes in the structure and/or activity of the medial thalamus (19,(94)(95)(96). These investigations are further supported by the high density of medial thalamic projections to frontal cortical regions, while other thalamic nuclei preferentially regulate activity of more parietal cortices (18,22,25,26,61,97). Here, we found a negative correlation between frontal spindles density and working memory performance that highlight the circuit specificity of our Opto-STROKE model and further supports the notion that these two phenomena might be functionally related and dependent on IL-PFC projections integrity (Figure 5M).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we found that stroke lesions in the IL induced significant changes in the thalamocortical connectivity, and, in particular, in the IL-to-ACC and -PL circuits including synaptic contacts onto parvalbumin-expressing cells (Figure 1G, H, I, J). It is possible that some of IL projections contact other cell types in these areas, however, previous reports have shown that the majority of them project towards inhibitory interneurons (18,26). Determining the exact contribution of IL-stroke to the changes in local cortical connectivity awaits further investigation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Given this evidence for HO TC induction of sustained depolarizations, HO thalamus could play a role in coordinating such transient ensembles of “prepared” neurons and sensitizing the cortex to additional synaptic inputs. One experimental difficulty in assessing HO TC’s impact in vivo that mass optogenetic excitation and inhibition does not lend itself to physiological stimulation patterns and it is likely that more naturalistic interventions will reveal nuances of the effect of HO TC projections–for example, the use of step-opsins by Mukherjee et al (2020) to show that enhancement of MD thalamus led to inhibition dominating activity in PFC.…”
Section: Higher-order Thalamocortical Projections To Cortexmentioning
confidence: 99%
“…The explanation starts from the debate about whether thalamus is merely a relay hub, or it is actually doing computation based on the signal from prefrontal cortex. A recent paper [14] compared the pathway of the medial geniculate body to A1 neurons and the pathway from MD to prelimbic prefrontal cortex, and this comparison shows distinctive functions in different areas of the thalamus. The former pathway is a sensory thalamic pathway, which affects the A1 circuit mainly through excitatory neurons, so it is just a first order thalamic nucleus.…”
Section: Introductionmentioning
confidence: 99%